Sistem Pendukung Keputusan Pemilihan Siswa Praktik Kerja Lapangan Terbaik Menggunakan Metode A New Additive Ratio Assessment - Megawaty, Dyah Ayu (CV. Keranjang Teknologi Media, 2024)
Student Field Work Practice (PKL) is an educational program that provides students with opportunities to gain work experience in an industrial or corporate environment. Through PKL, students can apply the knowledge they have learned in school in a real-world context, as well as gain an understanding of the work process and demands of a particular profession. The problem in this study is the difficulty in assessing the quality and potential of students holistically. Student performance evaluations are often based solely on academic achievement or previous work experience, which may not fully reflect the student's abilities and personality in the actual work environment. The purpose of this study is to implement the A New Additive Ratio Assessment method in the development of a decision support system to select the best PKL students. Using the A New Additive Ratio Assessment method, this study aims to identify and obtain optimal ratings from student candidates based on a number of predetermined criteria. Through the application of the A New Additive Ratio Assessment method provides an effective tool for decision makers, in selecting PKL students who best suit the needs and requirements set. The recommendation results show the rank of 1 best PKL student with an optimization function value of 0.9695, namely IS Students. These results can be a recommendation for companies in determining the Best PKL Students by applying the A New Additive Ratio Assessment method.